Does employee engagement mediate the influence of psychological contract breach on pro-environmental behaviors and intent to remain with the organization in the hotel industry? - Karatepe, Osman M.; Rezapouraghdam, Hamed; Hassannia, Raheleh (Routledge Journals, Taylor & Francis Ltd, 2021)
Drawing from psychological contract, job demands-resources, and affective events theories, this paper proposes and tests a research model where employee engagement (ENG) mediates the impact of psychological contract breach (PCB) on task-related pro-environmental behaviors (TPEBs), proactive pro-environmental behaviors (PPEBs), and intent to remain with the organization (IRO). The linkages given above were assessed via structural equation modeling. Based on data obtained from hotel customer-contact employees in three waves and their immediate supervisors in China, the findings reveal that PCB is a stressor eroding employee ENG, TPEBs, PPEBs, and proclivity to remain with the organization. Employees with high ENG display pro-environmental behaviors at high levels and exhibit elevated IRO. These findings implicitly illustrate that employee ENG partly mediates the impact of PCB on TPEBs, PPEBs, and proclivity to remain with the organization. Implications of these findings are discussed, as are the limitations and avenues for future research.
Keywords: China; employee engagement; hotel employees; intent to remain with the organization; pro-environmental behaviors; psychological contract breach